2011
DOI: 10.1108/20426761111141878
|View full text |Cite
|
Sign up to set email alerts
|

Predicting blood donation behaviour: further application of the theory of planned behaviour

Abstract: PurposeThe purpose of this paper is to test whether, in the context of blood donation, the predictive ability of the theory of planned behaviour (TPB) extends from behavioural intention to actual donation behaviour, and whether extended versions of the TPB perform better than the standard version.Design/methodology/approachIntentions to donate blood predicted by the TPB are compared with an accurate measure of blood donation behaviour obtained following a mobile blood drive by the New Zealand Blood Service.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
4
48
0
1
Order By: Relevance
“…Although participation in behaviours takes many forms and involves varying levels of intensity over time, behaviours are generally studied from a static perspective and often only intentions are studied rather than actual behavioural performance (Courneya & Bobick, ; Hansen et al, ). Given the gap between intentions and behaviours (Holdershaw et al, ) and that behaviour can be habituated, the omission of actual behaviour in health behaviour evaluations limits our understanding inflating the effect size for psychological constructs due to the absence of prior behaviours. Furthermore, consideration of behaviour change requires a temporal element to determine which factors are impacting behaviour over time.Hypothesis Intentions will positively influence physical activity behaviour.Hypothesis Intentions will positively influence healthful eating behaviour.…”
Section: Self‐efficacy Pbc and Experiencementioning
confidence: 99%
“…Although participation in behaviours takes many forms and involves varying levels of intensity over time, behaviours are generally studied from a static perspective and often only intentions are studied rather than actual behavioural performance (Courneya & Bobick, ; Hansen et al, ). Given the gap between intentions and behaviours (Holdershaw et al, ) and that behaviour can be habituated, the omission of actual behaviour in health behaviour evaluations limits our understanding inflating the effect size for psychological constructs due to the absence of prior behaviours. Furthermore, consideration of behaviour change requires a temporal element to determine which factors are impacting behaviour over time.Hypothesis Intentions will positively influence physical activity behaviour.Hypothesis Intentions will positively influence healthful eating behaviour.…”
Section: Self‐efficacy Pbc and Experiencementioning
confidence: 99%
“…Other authors also posit that the TPB does not address how people translate their intention into behaviour and therefore is unable to solve intention–behaviour discrepancies (Schwarzer, ). Holdershaw, Gendall, and Wright (), for example, found that intentions failed to align with behaviours when they used the TPB to explain blood donation behaviours. However, in the context of behaviour change interventions targeting physical activity, a meta‐analytic review by Hagger, Chatzisarantis, and Biddle () showed that the TPB exhibited a good fit for physical activity intentions and behaviour.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The TPB is one of the most common models used to examine blood donation and a variety of alternative TPB models have been used in various countries, including Canada, New Zealand, the United Kingdom, and the Netherlands, as well as Australia . Consequently, a range of variables and relationships that should be included within the broader TPB model have been proposed.…”
Section: Constructs and Numbers Of Items To Measure Constructs Withinmentioning
confidence: 99%